The Effect of Discipline and Work Ethic on the Performance of Elementary School Teachers in Sematang Borang Palembang - Sari, Ria Puspita; Fitria, Happy; Wahidy, Achmad (Jurnal Pendidikan Tambusai, 2021)
The purpose of the study is to know and to describe the effect of discipline and work ethic on the performance of Elementary School teachers in Sematang Borang Palembang. This research was conducted at Elementary School in Sematang Borang palembang. The type of research is used the quantitative research. The population of this study were 90 teachers. The data were collected through some steps; questionners, interviews, and documentation. The data were analized through multiple regression models by using SPSS for Windows programs. The result of this study conclude that partially work discipline has a positive and significant effect on performance of Elementary School teachers in Sematang Borang palembang. Meanwhile, simultaneously discipline and work ethic have a significant effect on the performance of Elementary School teachers